The correspondence of Charles Darwin - Darwin, Charles 1809-1882 (Cambridge University Press, 2015)
This volume is part of the definitive edition of letters written by and to Charles Darwin, the most celebrated naturalist of the nineteenth century. Notes and appendixes put these fascinating and wide-ranging letters in context, making the letters accessible to both scholars and general readers. Darwin depended on correspondence to collect data from all over the world, and to discuss his emerging ideas with scientific colleagues, many of whom he never met in person. The letters are published chronologically: Volume 23 includes letters from 1875, the year in which Darwin wrote and published Insectivorous plants, a botanical work that was a great success with the reading public, and started writing Cross and self fertilisation in the vegetable kingdom. The volume contains an appendix on the 1875 anti-vivisection debates, with which Darwin was closely involved, giving evidence before a Royal Commission on the subject.
Keywords: Darwin, Charles, -- 1809-1882 -- Correspondence.